Thin film nanocomposite (Tfnc) membranes: Future direction of Tfnc synthesis for alcohol dehydration - Mohamad Syafiq, Abdul Wahab; Alia Aqilah, Ghazali; Nurul Faizah, Abd Ghapar; Sunarti, Abd Rahman; Rozaimi, Abu Samah (Elsevier, 2021)
Polymeric membranes separation among the new and reliable separation and purification techniques in terms of energy consumption, ease of the process, and high selectivity due to polymer properties can be tailored to specific needs. This comprehensive review highlights polymeric membranes’ current development, specifically on thin film nanocomposite membranes for alcohol dehydration via pervaporation (PV). Discussion on substrate choice and fillers incorporating in respective polymers and how significant both materials in PV application has been scrutinized. Recent works on Thin Film Nanocomposite (TFNC) membranes showed that there is still a gap in factors or parameters involved in TFNC synthesis, which the same old weakness of membrane swelling, flux loss, and selectivity deficit seem left to be discovered. A performance plot of IPA dehydration from recent works has been provided within this paper as a benchmark for researchers to compare their findings. This review emphasizes on finding a set of parameter and nanomaterial as a possible approach for future TFNC development.